The Development of Pengempu Waterfall Cau Belayu Tabanan as One of Natural Objects Tourism in Tabanan Bali - Nita Kristiana Putri, Komang Shintiya (Jurnal Manajemen Pelayanan Hotel, 2023)
Pengempu Waterfall is one of the tourist attractions located in Cau Belayu Tourism Village, which is currently a tourist location that is busy being visited by local and foreign tourists. The purpose of this research is to describe the tourism potential of the Pengempu Waterfall and analyze the strategy for developing the attractiveness of the Pengempu Waterfall as a natural tourism in Cau Belayu Village. Data collection techniques used were observation, interviews, documentation and SWOT analysis to describe tourism potential and to formulate a tourism development strategy for Pengempu Waterfall. The data analysis technique used is the SWOT analysis technique, namely analyzing internal factors (strengths and weaknesses) and external factors (opportunities and threats) with the help of the SWOT matrix. The results of this study are that the strategy used in developing the Pengempu Waterfall as a natural tourism in Cau Belayu Tourism Village is the potential of 4 A, (attraction, amenity, accessibility and ancillary), with the role of stakeholders helping the development of tourism in Pengempu Waterfall using the SWOT strategy namely strengths, weaknesses, opportunities and threats. Keywords: Development Strategy, Tourism Potential, SWOT Analysis